(3MGTjI Ydi eNJUQ GdeYGeis - (3eLghds ((3eMeO QVG s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje bhdg fMeOc Gddge BKQ MeO Gddg Ydi GdTcQ dCf GdMeO s
(3BNQgG (B:s
(3hVYJ HGdEZQGR ai UOQ GdUOQjI GdefUhHI eG JaM GdUhQjI hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdeLGejYs